Emerging Market Potential for Organic Farming Products - Hendro Prasetyo; Rahayu Relawati; Barbara Szymoniuk; Nur Baladina (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2023)
Organic farming products need to be targeted towards specific market segments, particularly consumers who prioritize health and environmental concerns. However, the specialized market for organic agricultural products in Kota Batu is still in its infancy. This study aims to achieve the following research objectives: 1) assessing the potential and challenges of organic farming development, 2) identifying clusters within the organic farming sector, 3) developing an effective marketing system for organic farming products, and 4) determining optimal market locations for selling organic produce. The research was conducted in Kota Batu, East Java, in 2019, utilizing primary data gathered from farmers in fourteen villages. Quantitative descriptive analysis and the Analytical Hierarchy Process were employed to address the research objectives. The findings revealed the existence of organic farming clusters, including food crops (rice and corn), plantations (coffee), and horticulture (vegetables, fruits, and biopharmaceuticals). To develop the marketing system for organic agricultural products, emphasis was placed on organic certification, enhancing both the quality and quantity of products. Location development involved the centralization of markets, establishment of outlets for organic farming products, and improvements to infrastructure and facilities. To promote organic farming products, efforts were made to strengthen information dissemination through various media channels and foster a sense of community among consumers of organic farming products. The Town Square of Kota Batu and Central Market Batu emerged as the most strategically advantageous locations for marketing organic farming products, owing to their convenient accessibility for consumers